Interpreting Islamic Education For Social Change: Hasan Al-Turabi's Views on Women's Rights And Gender Equality - Ahmad Nabilul Maram; Husein Aziz; M. Ridlwan Nasir (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
The research examines the intellectual journey of Hasan al-Turabi regarding gender and the role of women in Islam. Al-Turabi, an influential Muslim scholar, demonstrates the evolution of his perspectives across several dimensions. This study analyzes Al-Turabi's progressive views on women's role and political participation and their impact on Sudan's Islamic women's movement. However, there is controversy concerning his opinions on leadership, female testimony in Islamic law, and polygamy. This research also illustrates how interpretations of religious teachings shape perceptions of gender equality and the role of religion in initiating social change. Al-Turabi encourages the Muslim community to reexamine sacred texts within the context of the modern era, seeking egalitarian values that align with the spirit of Islam. This exploration highlights the complexity of debates surrounding religion and tradition in the context of social change while promoting a broader understanding of the dynamics of contemporary Muslim societies.